منح مولانا البَارِي في مناقب أَبِي القَاسمِ السَّكَنْدَرِيِّ القَبَّارِيِّ تحقيق ودراسة : [Mīnah Mawlānā al-Bārī fī Manāqib Abī al-Qāsim al-Sakandarī al-Qabbārī: Edition and Study] - Nāṣir al-Dīn b. al-Munīr (Islamic Sources / Maṣādir Islāmiyya, 2026)
ناصِرُ الدِّين ابنُ المُنيِّر تلميذٌ وفيٌّ مُخلِصٌ لأبي القاسِم للقَبَّاريِّ، سجَّل تفاصيلَ حياته؛ كي تكون تطبيقاتٍ عمليّةً لتعاليم القُرآن الكريم والسُّنّة الشَّريفة، من دُون ابتداعٍ. كان القَبَّاريُّ دقيقًا في القول والعمل، مُتحرِّيًا في التَّمييز بين الحلال والحَرام، مُحترِزًا من إدْخال طعامٍ أو شَرَابِ في الجَوْف إلَّا من أبْواب الحلال، مُتيقِّظًا في مُعامَلة النّاس؛ حتَّى لا يُؤذي أحدَهم أو يُضِرُّه ولو بأقلِّ القليل. فحرَص ابنُ المُنيِّر على إبْرازها في هذا العَمَل الذي كتَبَه كشاهِد عِيَانٍ، مُعاصِر لها بنفسه، غير مُجامِلٍ لشَيْخه أو مُبالِغ في حُبِّه له. Nāṣir al-Dīn b. al-Munīr was a loyal and sincere student of Abī al-Qāsim al-Qabbārī. He recorded the details of al-Qabbārī's life to serve as practical applications of the teachings of the Qur'ān and the Sunnah- without innovation. Al-Qabbārī was precise in both speech and action, meticulous in distinguishing between the lawful (ḥalāl) and the unlawful (ḥarām), and cautious about allowing any food or drink into his body except that is earned in a ḥalāl ways . He was vigilant in his dealings with people, ensuring that he did not harm or hurt anyone, even in the slightest way. Ibn al-Munīr was keen to highlight this in the work he wrote, as a firsthand witness to these actions, without flattering his teacher or exaggerating his love for him.